A new species of Acalypha (Euphorbiaceae) from Guerrero, Mexico - Martínez-Gordillo, Martha; Fragoso-Martínez, Itzi; Velasco-Gutiérrez, Kenia (Phytotaxa, 2022)
Acalypha amithii is described and illustrated as a new species from the State of Guerrero, Mexico. Its distribution is restricted to the Pacific slope. Acalypha amithii is morphologically close to the Mesoamerican A. ferdinandi and the South American A. stenoloba. However, it can be distinguished from the former by number of teeth in the bracts of the pistillate flowers (13–15 vs. 7 in the new species) and from the latter by the degree of fusion of the sepals of the pistillate flowers (connate at the base vs. free in the new species). Acalypha amithii is characterized by a suffruticose habit, penninerved leaves, terminal or axillary pistillate inflorescences, sepals of the pistillate flowers completely free and ovate-lanceolate, bracts of the pistillate flowers cuneate at the base, styles glabrous and almost 12 times longer than the ovary.